Analysis Strategy Online Learning of Applied Mathematics at Civil Engineering of Politeknik Negeri Malang - Dewi, Mutia Lina; Khusniah, Rif'atul; Maghfiroh, Rofila El (Proceeding International Conference on Mathematics and Learning Research, 2021)
This study used a qualitative approach with the object of research was the second semester students of the Construction Engineering Management for the 2021/2022 academic year, class 1TRKJJ1 as the research subject. The research instrument consisted of test scores, questionnaires, and discussions between mathematics lecturers from the other departments. The purpose of this research is to find the online mathematics learning strategy. The results showed that the average score of the mathematics test for class 1TRKJJ1 was Test 1 = 98 by random multiple choice questions and Test 2 = 76 by essay questions. Many students cheat, it can be seen from the same answers. Mathematics lecturers are required to provide a variety of applications, correcting carefully because many answers are correct but the process are mistakes due to writing errors. The results of the mathematics lecturer's questionnaire were 42.9% math allocation 2 hours/semester, 85.7 % zoom meetings, 71.4% making learning videos, 0% you tube, 71.4% discussing questions with student presentations, 100% experiencing internet network problems, and 57.1% giving essay test questions. The results of the discussion between mathematics lecturers about assessment were that students presented individual presentations when answering practice questions, different test questions, handwritten answers, many questions are given, and students choose their own questions, each answer has the student's signature. The learning strategy are (1) use various applications such as zoom, google. meet, and google classroom, (2) use application facilities such as white board, share, and video, (3) give a test with different questions and handwritten.